The integration of technological sources through online activities used for educational purposes in order to promote critical thinking skills among students in high school - Araya Córdoba, Wendell (2021)
Education is an essential pillar that is constantly changing and evolving according to society’s needs. Therefore, teachers need to be learning new strategies and methods to help students acquire the knowledge and skills they will eventually need once they become adults and look for a job. An example of a skill that needs to be mastered nowadays by the students is critical thinking. In other words, students need to improve their ability to analyze, synthesize, judge, and debate the information they come across in order to set connections between ideas and facts. Therefore, teachers have the challenging duty to find out ways to foster critical thinking among students and that is where technology takes place as a tool to lighten the load. Hence, the use of technology can help teachers catch students’ attention and make the classes more appealing for them, not to mention that their participation can be boosted which will also contribute to foster critical thinking. Lastly, some proposals that incorporate the use of technology and can be used to foster critical thinking are online discussion forums, Online PBls (Project based learning), WebQuest as well as the use of YouTube and Web based learning software such as Blackboard.